Etnomatematika : Eksplorasi Konsep Geometri Pada Bangunan Meru di Bali - Nabilah Nada Asyifa; Khafriza Faiqotuz Zahro; Nagita Elsafia; Abdul Majid; Abdul Majid (Journal Innovation In Education, 2024)
This article explores Ethnomathematics in the context of the geometric concepts embodied in the Meru buildings of Bali. The Meru structure holds significant symbolic value for the Balinese community, incorporating various elements of local customs and predominant religious beliefs. The primary focus of this research is to identify the geometric shapes and the symbolic meanings embedded within them. Utilizing an ethnographic approach, the study incorporates observations and literature reviews from several articles related to Meru. The analysis reveals that the geometric elements within Meru structures encompass not only flat shapes but also three-dimensional forms. Furthermore, the literature review highlights the symbolic representations of the beliefs and traditions of the Balinese people.